Thermoelectric conversion material, thermoelectric conversion element, and thermoelectric conversion module

JP7631702B2Active Publication Date: 2025-02-19MITSUBISHI MATERIALS CORP
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
JP2020134901
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-12-24
Filing Date
2020-08-07
Publication Date
2025-02-19
Estimated Expiration
2040-08-07

AI Technical Summary

Benefits of technology

【0018】 本発明によれば、熱電特性、耐酸化性、強度に優れた熱電変換材料、および、この熱電変換材料を用いた熱電変換素子、および、熱電変換モジュールを提供することが可能となる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007631702000011
    Figure 0007631702000011
  • Figure 0007631702000012
    Figure 0007631702000012
  • Figure 0007631702000013
    Figure 0007631702000013
Patent Text Reader

Abstract

To provide a thermoelectric conversion material excellent in thermoelectric characteristics, oxidation resistance and strength, a thermoelectric conversion element using the thermoelectric conversion material, and a thermoelectric conversion module.SOLUTION: A thermoelectric conversion material contains Mg2SiXSn1-X(0.3≤X≤1), and a boride including one or more metals selected from titanium, zirconium, and hafnium. Further, the boride is preferably one or more selected from TiB2, ZrB2, and HfB2.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This invention is Mg2Si X Sn 1-X (where 0.3≦X≦1) as a main component, a thermoelectric conversion material, a thermoelectric conversion element, and a thermoelectric conversion module. [Background technology]

[0002] Thermoelectric conversion elements made of thermoelectric conversion materials are electronic elements that can convert between heat and electricity using the Seebeck effect and Peltier effect. The Seebeck effect is the effect of converting thermal energy into electrical energy, and is the phenomenon in which an electromotive force is generated when a temperature difference is created between both ends of a thermoelectric conversion material. This electromotive force is determined by the properties of the thermoelectric conversion material. In recent years, there has been active development of thermoelectric power generation that utilizes this effect. The above-mentioned thermoelectric conversion element has a structure in which electrodes are formed on one end side and the other end side of a thermoelectric conversion material.

[0003] As an index expressing the characteristics of such a thermoelectric conversion element (thermoelectric conversion material), for example, the power factor (PF) expressed by the following formula (1) and the dimensionless figure of merit (ZT) expressed by the following formula (2) are used. Note that in a thermoelectric conversion material, it is necessary to maintain a temperature difference between one end and the other end, so low thermal conductivity is preferable. PF=S 2 σ (1) Where, S: Seebeck coefficient (V / K), σ: electrical conductivity (S / m) ZT=S 2 σT / κ (2) where T = absolute temperature (K), κ = thermal conductivity (W / (m×K)).

[0004] As the above-mentioned thermoelectric conversion material, for example, as disclosed in Patent Document 1, magnesium silicide to which various dopants have been added has been proposed. Here, the above-mentioned thermoelectric conversion material made of magnesium silicide tends to be easily oxidized, and the oxidation may deteriorate the thermoelectric properties or make the element brittle. For this reason, for example, Patent Document 2 proposes a technique for preventing oxidation of a thermoelectric conversion material by covering the thermoelectric conversion material with glass. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2013-179322 A [Patent Document 2] JP 2017-050325 A Summary of the Invention [Problem to be solved by the invention]

[0006] However, as shown in Patent Document 2, when the thermoelectric conversion material is covered with glass, the glass may peel off due to the difference in thermal expansion coefficient between the thermoelectric conversion material and the glass, and oxidation of the thermoelectric conversion material may not be suppressed. In addition, the entire surface of the thermoelectric conversion material constituting each thermoelectric conversion element needs to be covered with glass, which increases the manufacturing cost. Furthermore, magnesium silicide is a brittle material and may crack during handling.

[0007] The present invention has been made in consideration of the above-mentioned circumstances, and aims to provide a thermoelectric conversion material having excellent thermoelectric properties, oxidation resistance, strength, and fracture toughness, and a thermoelectric conversion element and a thermoelectric conversion module using this thermoelectric conversion material. [Means for solving the problem]

[0008] In order to solve the above problems, the thermoelectric conversion material of the present invention is Mg2Si X Sn 1-X (however 0.35≦X≦1) and a boride containing one or more metals selected from titanium, zirconium, and hafnium, Thermoelectric materials The total content of the borides relative to 3.0 mass% or more and 9.8 mass% or less The characteristic of this method is that it is within the range of

[0009] According to the thermoelectric conversion material having this configuration, since it contains a boride containing one or more metals selected from titanium, zirconium, and hafnium, this boride becomes the parent phase of Mg2Si X Sn 1-X By agglomerating these at the grain boundaries, electrical conductivity is improved, making it possible to improve the power factor (PF), which is one of the indicators of thermoelectric properties. Furthermore, since the boride contains one or more metals selected from titanium, zirconium and hafnium, oxidation of magnesium can be suppressed, and oxidation resistance can be improved. Furthermore, since the above-mentioned borides are relatively hard and have high strength, the strength of the thermoelectric conversion material can be improved, and the occurrence of cracks during handling can be suppressed. The total content of the borides is 3.0 mass% or more and 9.8 mass% or less Since the range is set to be within this range, it is possible to sufficiently improve the thermoelectric characteristics, oxidation resistance, and strength.

[0010] Here, in the thermoelectric conversion material of the present invention, the Mg2Si X Sn 1-X may be magnesium silicide with X=1. In this case, even if the parent phase is composed of magnesium silicide (Mg2Si), the thermoelectric properties, oxidation resistance, strength, and fracture toughness are sufficiently excellent.

[0011] In the thermoelectric conversion material of the present invention, the boride is preferably one or more selected from TiB2, ZrB2, and HfB2. In this case, since the boride is one or more selected from TiB2, ZrB2, and HfB2, it is possible to reliably improve the thermoelectric characteristics, oxidation resistance, and strength.

[0014] In addition, the thermoelectric conversion material of the present invention further contains aluminum. The content of the aluminum in the thermoelectric conversion material is within a range of 0.05 mass% or more and 1 mass% or less. It is preferred. In this case, the addition of aluminum can further improve the thermoelectric properties, oxidation resistance, and mechanical strength.

[0015] Also, Since the content of the aluminum in the thermoelectric conversion material is within the above-mentioned range, it is possible to reliably improve the thermoelectric characteristics, oxidation resistance, and mechanical strength.

[0016] A thermoelectric conversion element of the present invention is characterized by comprising the above-mentioned thermoelectric conversion material and electrodes joined to one surface and the other surface of the thermoelectric conversion material, respectively. According to the thermoelectric conversion element having this configuration, since the above-mentioned thermoelectric conversion material having excellent thermoelectric properties, oxidation resistance, and strength is included, various characteristics are stable, and therefore the thermoelectric conversion performance is stable and the reliability is excellent.

[0017] A thermoelectric conversion module of the present invention is characterized by comprising the above-mentioned thermoelectric conversion element and terminals joined to the electrodes of the thermoelectric conversion element, respectively. According to the thermoelectric conversion module having this configuration, since it includes the above-mentioned thermoelectric conversion element, the thermoelectric conversion material has excellent thermoelectric properties, oxidation resistance, and strength, and various properties are stable, so that the thermoelectric conversion performance is stable and the reliability is excellent. Effect of the Invention

[0018] According to the present invention, it is possible to provide a thermoelectric conversion material having excellent thermoelectric properties, oxidation resistance, and strength, and a thermoelectric conversion element and a thermoelectric conversion module using this thermoelectric conversion material. [Brief description of the drawings]

[0019] [Figure 1] 1 is a cross-sectional view of a thermoelectric conversion material, a thermoelectric conversion element, and a thermoelectric conversion module according to an embodiment of the present invention. [Diagram 2] FIG. 1 is a flow diagram of a method for producing a thermoelectric conversion material according to an embodiment of the present invention. [Diagram 3] FIG. 2 is a cross-sectional view showing an example of a sintering apparatus used in the method for producing a thermoelectric conversion material according to the embodiment of the present invention. [Figure 4] FIG. 4 is a flow diagram of a method for producing a thermoelectric conversion material according to another embodiment of the present invention. [Diagram 5] 1 is an external observation photograph showing the results of evaluating oxidation resistance in an example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] Hereinafter, the thermoelectric conversion material, thermoelectric conversion element, and thermoelectric conversion module according to the embodiments of the present invention will be described with reference to the attached drawings. Note that the following embodiments are specifically described to better understand the gist of the invention, and do not limit the present invention unless otherwise specified. In addition, the drawings used in the following description may show the main parts enlarged for convenience in order to easily understand the features of the present invention, and the dimensional ratios of each component may not necessarily be the same as the actual ones.

[0021] FIG. 1 shows a thermoelectric conversion material 11 according to an embodiment of the present invention, and a thermoelectric conversion element 10 and a thermoelectric conversion module 1 that use this thermoelectric conversion material 11. This thermoelectric conversion element 10 includes a thermoelectric conversion material 11 according to this embodiment, and electrodes 18a, 18b formed on one surface 11a and the other surface 11b of this thermoelectric conversion material 11. The thermoelectric conversion module 1 also includes terminals 19a and 19b joined to the electrodes 18a and 18b of the thermoelectric conversion element 10 described above, respectively.

[0022] The electrodes 18a, 18b are made of nickel, silver, cobalt, tungsten, molybdenum, etc. The electrodes 18a, 18b can be formed by electric current sintering, plating, electrodeposition, etc. The terminals 19a, 19b are formed from a metal material having excellent conductivity, such as a plate material of copper or aluminum. In this embodiment, a rolled aluminum plate is used. The thermoelectric conversion element 10 (electrodes 18a, 18b) and the terminals 19a, 19b can be joined by Ag solder, Ag plating, or the like.

[0023] The thermoelectric conversion material 11 of this embodiment is Mg2Si X Sn 1-X (where 0.3≦X≦1) is the main component of the sintered body. Here, the thermoelectric conversion material 11 is undoped Mg2Si X Sn 1-X or Mg2Si containing one or more dopants selected from Li, Na, K, B, Ga, In, N, P, As, Sb, Bi, Ag, Cu, and Y. X Sn 1-X The second embodiment may be configured as follows:

[0024] In this embodiment, the thermoelectric conversion material 11 is Mg2Si X Sn 1-X The mass percentage of Mg2Si is 50 mass% or more and 99.5 mass% or less. X Sn 1-X is said to have antimony (Sb) added as a dopant. For example, the thermoelectric conversion material 11 of this embodiment is Mg2Si X Sn 1-X The composition contains antimony in a range of 0.1 atomic % to 2.0 atomic % inclusive. Note that, by adding antimony, which is a pentavalent donor, the thermoelectric conversion material 11 of this embodiment is made into an n-type thermoelectric conversion material with high carrier density.

[0025] Here, as a donor for making the thermoelectric conversion material 11 into an n-type thermoelectric conversion element, other than antimony, bismuth, phosphorus, arsenic, etc. can be used. Furthermore, the thermoelectric conversion material 11 may be a p-type thermoelectric conversion element, and in this case, a dopant such as lithium or silver may be added as an acceptor to obtain a p-type thermoelectric conversion element.

[0026] The thermoelectric conversion material 11 of this embodiment contains a boride containing one or more metals selected from titanium, zirconium, and hafnium, which are group 4 elements. Examples of the above-mentioned borides include TiB2, ZrB2, and HfB2. These borides are formed by mixing Mg2Si X Sn 1-X It is preferable that the particles are aggregated at the grain boundaries.

[0027] In this embodiment, the total content of the above-mentioned borides is preferably within the range of 0.5 mass % or more and 15 mass % or less. The lower limit of the total content of the above-mentioned borides is more preferably 1 mass% or more, and even more preferably 1.5 mass% or more. On the other hand, the upper limit of the total content of the above-mentioned borides is more preferably 12 mass% or less, and even more preferably 10 mass% or less.

[0028] The thermoelectric conversion material 11 of this embodiment may contain aluminum. The inclusion of aluminum leads to further improvements in thermoelectric properties, oxidation resistance and mechanical strength. Here, the amount of aluminum added is preferably within the range of 0.01 mass % to 1 mass %.

[0029] Next, a method for producing the thermoelectric conversion material 11 according to this embodiment will be described with reference to FIGS.

[0030] (Lump magnesium silicide compound formation process S01) First, Mg2Si which is the parent phase of the sintered body which is the thermoelectric conversion material 11 X Sn 1-X The magnesium silicide compound is formed as a raw material for the above process. In the lump magnesium silicide compound forming step S01, silicon powder, magnesium powder, and tin powder and dopant added as necessary are each weighed and mixed. For example, when forming an n-type thermoelectric conversion material, a pentavalent material such as antimony or bismuth is mixed as a dopant, and when forming a p-type thermoelectric conversion material, a material such as lithium or silver is mixed as a dopant. Note that undoped Mg2Si without adding a dopant can be obtained. X Sn 1-X It is also possible to use the following. In this embodiment, antimony is used as a dopant to obtain an n-type thermoelectric conversion material, and the amount of antimony added is set within the range of 0.1 atomic % to 2.0 atomic %.

[0031] Then, this mixed powder is introduced into, for example, an alumina crucible, and the sintering raw material powder is Mg2Si X Sn 1-X In the case of (X=1), the temperature is increased to a range of 800℃ to 1150℃, and the sintering raw powder becomes Mg2Si X Sn 1-X In the case of (0.3≦X<1), the mixture is heated to a temperature range of 700° C. to 900° C., and then cooled to solidify, thereby obtaining a lump magnesium silicide compound. Since a small amount of magnesium sublimes upon heating, it is preferable to add, when measuring the raw materials, an amount of magnesium that is, for example, 3 atomic % to 5 atomic % more than the stoichiometric composition.

[0032] (Crushing process S02) Next, the obtained lump magnesium silicide compound was pulverized by a pulverizer to obtain magnesium silicide compound powder (MgSi X Sn 1-X Form a powder. In this pulverization step S02, it is preferable that the average particle size of the magnesium silicide compound powder is set within a range of 1 μm or more and 100 μm or less. In addition, in the magnesium silicide compound powder to which a dopant has been added, the dopant is uniformly present in the magnesium silicide compound powder.

[0033] When using a commercially available magnesium silicide compound powder or a magnesium silicide compound powder to which a dopant is added, the lump magnesium silicide compound forming step S01 and the pulverizing step S02 can be omitted.

[0034] (Sintering raw powder formation process S03) Next, the obtained magnesium silicide compound powder is mixed with boride powder containing one or more metals selected from titanium, zirconium, and hafnium to obtain a sintering raw material powder. Aluminum powder may be added as necessary. Here, the content of the boride powder in the sintering raw material powder is preferably within a range of 0.5 mass% to 15 mass%. The boride powder preferably has a purity of 99 mass% or more. The average particle size of the boride powder is preferably within a range of 1 μm to 100 μm. When aluminum powder is added, the content of aluminum powder in the sintering raw material powder is preferably within the range of 0.01 mass% to 1 mass%. The purity of the aluminum powder used is preferably 99.99 mass% or higher. Furthermore, the average particle size of the aluminum powder is preferably within the range of 1 μm to 100 μm.

[0035] (Sintering process S04) Next, the sintering raw material powder obtained as described above is heated while being pressurized to obtain a sintered body. In this embodiment, the sintering step S04 uses a sintering apparatus (electric current sintering apparatus 100) shown in FIG. The sintering apparatus (electrical sintering apparatus 100) shown in FIG. 3 includes, for example, a pressure-resistant housing 101, a vacuum pump 102 for reducing the pressure inside the pressure-resistant housing 101, a hollow cylindrical carbon mold 103 arranged in the pressure-resistant housing 101, a pair of electrodes 105a, 105b for applying current while pressurizing the sintering raw material powder Q filled in the carbon mold 103, and a power supply device 106 for applying a voltage between the pair of electrodes 105a, 105b. A carbon plate 107 and a carbon sheet 108 are arranged between the electrodes 105a, 105b and the sintering raw material powder Q, respectively. In addition, a thermometer, a displacement gauge, and the like (not shown) are also included. In this embodiment, a heater 109 is arranged on the outer periphery of the carbon mold 103. The heater 109 is arranged on the four side surfaces so as to cover the entire outer periphery of the carbon mold 103. The heater 109 may be a carbon heater, a nichrome wire heater, a molybdenum heater, a Kanthal wire heater, a high-frequency heater, or the like.

[0036] In the sintering step S04, first, the sintering raw material powder Q is filled into the carbon mold 103 of the electric sintering apparatus 100 shown in FIG. 3. The carbon mold 103 is covered with, for example, a graphite sheet or a carbon sheet. Then, a direct current is applied between the pair of electrodes 105a, 105b using the power supply device 106, and the temperature is increased by self-heating by applying a current to the sintering raw material powder Q. In addition, the movable electrode 105a of the pair of electrodes 105a, 105b is moved toward the sintering raw material powder Q, and the sintering raw material powder Q is pressurized at a predetermined pressure between the electrode 105b on the fixed side. In addition, the heater 109 is heated. As a result, the powdered sintering raw material Q is sintered by the self-heating of the powdered sintering raw material Q, the heat from the heater 109, and the pressure.

[0037] In this embodiment, the sintering conditions in the sintering step S04 are as follows: the sintering raw material powder Q is Mg2Si X Sn 1-X In the case of (X=1), the sintering temperature is within the range of 800℃ to 1020℃, and the sintering raw material powder Q is Mg2Si X Sn 1-XIn the case of (0.3≦X<1), the sintering temperature is within the range of 600° C. or higher and 800° C. or lower, and the holding time at each sintering temperature is 10 minutes or less. In addition, the pressure load is set to be within the range of 20 MPa or more and 50 MPa or less. The atmosphere inside pressure-resistant housing 101 may be an inert atmosphere such as an argon atmosphere or a vacuum atmosphere. If a vacuum atmosphere is used, the pressure should be 5 Pa or less.

[0038] Here, the sintering raw material powder Q (Mg2Si X Sn 1-X (X=1)) is sintered at a temperature lower than 800°C, or when the sintering raw material powder Q (Mg2Si X Sn 1-X If the sintering temperature (0.3≦X<1)) is less than 600°C, the oxide film formed on the surface of each powder of the sintered raw material powder Q cannot be sufficiently removed, and the surface oxide film of the raw material powder itself remains at the grain boundaries, and the bonding between the raw material powders is insufficient, resulting in a low density sintered body. For these reasons, the electrical resistance of the obtained thermoelectric conversion material may be high. In addition, the strength of the element may be low due to the insufficient bonding. On the other hand, sintering raw material powder Q (Mg2Si X Sn 1-X (X=1)) exceeds 1020℃, or the sintering raw material powder Q (Mg2Si X Sn 1-X When the sintering temperature of (0.3≦X<1)) exceeds 800℃, Mg2Si X Sn 1-X The decomposition of (0.3≦X≦1) may proceed in a short period of time, causing a deviation in composition, which may result in an increase in electrical resistance and a decrease in the Seebeck coefficient.

[0039] For this reason, in this embodiment, the sintering temperature in the sintering step S04 is set to 1000° C. X Sn 1-X In the case of (X=1), the sintering temperature is 800℃ to 1020℃, and the sintering raw material powder Q (Mg2Si X Sn 1-XIn the case of (0.3≦X<1), the temperature is set within the range of 600°C or more and 800°C or less. In addition, the sintering raw material powder Q (MgSi X Sn 1-X The lower limit of the sintering temperature of the raw material powder Q (Mg2Si X Sn 1-X The upper limit of the sintering temperature (X=1) is preferably 1020° C. or lower, and more preferably 1000° C. or lower. In addition, the sintering raw material powder Q (MgSi X Sn 1-X The lower limit of the sintering temperature (0.3≦X<1) is preferably 650°C or higher. X Sn 1-X The upper limit of the sintering temperature (0.3≦X<1) is preferably 770° C. or lower, and more preferably 740° C. or lower.

[0040] Also, if the holding time at the sintering temperature exceeds 10 minutes, Mg2Si X Sn 1-X This may cause the decomposition of the ferroelectric material to progress, resulting in a deviation in composition, an increase in electrical resistance, and a decrease in the Seebeck coefficient. Furthermore, the particles may become coarse, resulting in an increase in thermal conductivity. For this reason, in this embodiment, the holding time at the sintering temperature in the sintering step S04 is set to 10 minutes or less. The upper limit of the holding time at the sintering temperature in the sintering step S04 is preferably 5 minutes or less, and more preferably 3 minutes or less.

[0041] Furthermore, if the pressure load in the sintering step S04 is less than 20 MPa, the density will not be high, and the electrical resistance of the thermoelectric conversion material may be high, and the strength of the element may not be increased. On the other hand, if the pressure load in the sintering step S04 exceeds 50 MPa, the force acting on the carbon jig is so large that the jig may break. For this reason, in this embodiment, the pressure load in the sintering step S04 is set within the range of 20 MPa or more and 50 MPa or less. The lower limit of the pressure load in the sintering step S04 is preferably 23 MPa or more, more preferably 25 MPa or more, while the upper limit of the pressure load in the sintering step S04 is preferably 50 MPa or less, more preferably 45 MPa or less.

[0042] Through the above steps, the thermoelectric conversion material 11 of this embodiment is manufactured.

[0043] According to the thermoelectric conversion material 11 of the present embodiment having the above-mentioned configuration, since it contains a boride containing one or more metals selected from titanium, zirconium, and hafnium, the boride is a matrix phase of Mg2Si X Sn 1-X By agglomerating at the grain boundaries, electrical conductivity is improved, making it possible to improve the power factor (PF), which is one of the indicators of thermoelectric properties. Furthermore, since the boride contains one or more metals selected from titanium, zirconium and hafnium, oxidation of magnesium can be suppressed, and oxidation resistance can be improved. Furthermore, the above-mentioned borides are relatively hard and have high strength, so Mg2Si X Sn 1-X It is possible to improve the strength of the sintered body containing this as the main component, and it is possible to suppress the occurrence of cracks during handling.

[0044] In addition, in this embodiment, when the total content of the above-mentioned borides is within the range of 0.5 mass % or more and 15 mass % or less, it is possible to sufficiently improve the thermoelectric characteristics, oxidation resistance, and strength. Furthermore, in this embodiment, when the above-mentioned boride is one or more selected from TiB2, ZrB2, and HfB2, it is possible to reliably improve the thermoelectric characteristics, oxidation resistance, and strength.

[0045] In this embodiment, the thermoelectric conversion material 11 is Mg2Si X Sn 1-X When the mass percentage of is within the range of 50 mass % or more and 99.5 mass % or less, sufficient thermoelectric properties can be ensured. Furthermore, in this embodiment, when the thermoelectric conversion material 11 contains aluminum, it is possible to further improve the thermoelectric characteristics, oxidation resistance, and mechanical strength.

[0046] Furthermore, the thermoelectric conversion element 10 and the thermoelectric conversion module 1 of this embodiment include the above-mentioned thermoelectric conversion material 11, which has excellent thermoelectric properties, oxidation resistance, and strength, and therefore the various properties are stable. Therefore, the thermoelectric conversion performance is stable and the reliability is excellent.

[0047] Although the embodiment of the present invention has been described above, the present invention is not limited to this, and can be modified as appropriate without departing from the technical concept of the invention. For example, in the present embodiment, a thermoelectric conversion module having a structure as shown in FIG. 1 is described, but this is not limited thereto, and there are no particular limitations on the structure and arrangement of the electrodes and terminals as long as the thermoelectric conversion material of the present invention is used.

[0048] In this embodiment, as shown in FIG. 2, magnesium silicide compound powder (MgSi X Sn 1-XIn the above description, the sintering raw material powder is formed by adding boride powder to the magnesium powder, but the present invention is not limited to this. As shown in FIG. 4, magnesium powder, silicon powder (tin powder as necessary), and boride powder are mixed, and the mixed powder is introduced into, for example, an alumina crucible, heated to a temperature within the range of 800°C to 1150°C, or within the range of 700°C to 900°C (when tin powder is added), and cooled to solidify. The obtained magnesium silicide compound lump (MgSi X Sn 1-X ) may be pulverized to form the sintering raw material powder.

[0049] In addition, in this embodiment, sintering is performed using the sintering apparatus (electric current sintering apparatus 100) shown in FIG. 3, but this is not limited to this, and a method of sintering by indirectly heating and pressurizing the sintering raw material, such as hot pressing or HIP (Hot Isotactic Pressing), may also be used.

[0050] Furthermore, in this embodiment, a magnesium silicide compound powder (MgSi X Sn 1-X In the above description, the sintering raw material is described as being made of Li, Na, K, B, Ga, In, N, P, As, Sb, Bi, Ag, Cu, or Y. However, the sintering raw material is not limited to this, and may contain, for example, one or more dopants selected from Li, Na, K, B, Ga, In, N, P, As, Sb, Bi, Ag, Cu, or Y, or may contain these elements in addition to Sb. In addition, we have developed a non-doped magnesium silicide compound (MgSi X Sn 1-X ) may be a sintered body. EXAMPLES

[0051] The results of experiments carried out to confirm the effects of the present invention will be described below.

[0052] Example 1 In this Example 1, the thermoelectric properties of a thermoelectric conversion material containing magnesium silicide (Mg2Si) as a main component were evaluated. Mg with a purity of 99.9 mass% (particle size 180 μm: manufactured by Kojundo Chemical Laboratory Co., Ltd.), Si with a purity of 99.99 mass% (particle size 300 μm: manufactured by Kojundo Chemical Laboratory Co., Ltd.), and Sb with a purity of 99.9 mass% (particle size 300 μm: manufactured by Kojundo Chemical Laboratory Co., Ltd.) were prepared, weighed, mixed well in a mortar, placed in an alumina crucible, and heated in Ar-3 vol% H2 at 850°C for 2 hours. In consideration of deviation from the stoichiometric composition of Mg:Si=2:1 due to sublimation of Mg, 5 atomic % more Mg was mixed. As a result, block magnesium silicide (Mg2Si) with the composition shown in Table 1 was obtained. Next, this lump magnesium silicide (Mg2Si) was crushed into fine powder in a mortar and classified to obtain magnesium silicide powder (Mg2Si powder) with an average particle size of 30 μm.

[0053] Also, boride powder (purity 99.9 mass%, average particle size 3 μm) shown in Table 1 was prepared. This was weighed so as to obtain the content shown in Table 1, and the magnesium silicide powder and boride powder were mixed to obtain a sintering raw material powder. The obtained sintering raw material powder was filled into a carbon mold the inside of which was covered with a carbon sheet, and electric current sintering was performed under the conditions shown in Table 1 using the sintering apparatus (electric current sintering apparatus 100) shown in FIG.

[0054] The obtained sintered body was cut into a predetermined size using a diamond band saw, and the surface of the cut sintered body was polished with sandpaper of various grits to obtain a thermoelectric conversion material having the composition shown in Table 1. The thermoelectric conversion materials obtained as described above were evaluated for thermal conductivity κ, power factor PF, and dimensionless figure of merit ZT at various temperatures. The evaluation results are shown in Table 1.

[0055] The resistivity R and the Seebeck coefficient S were measured using a ZEM-3 manufactured by Advance Riko Co., Ltd. The resistivity R and the Seebeck coefficient S were measured at 100°C, 200°C, 300°C, 400°C, and 500°C. The power factor (PF) was calculated using the following formula (1). PF=S 2 / R···(1) where S is the Seebeck coefficient (V / K) and R is the resistivity (Ω m).

[0056] Thermal conductivity κ was calculated by multiplying thermal diffusivity by density by specific heat capacity. Thermal diffusivity was measured using a thermal constant measuring device (TC-7000, manufactured by Shinku Riko Co., Ltd.), density was measured using the Archimedes method, and specific heat was measured using a differential scanning calorimeter (DSC-7, manufactured by PerkinElmer Co., Ltd.). Measurements were performed at 25°C, 100°C, 200°C, 300°C, 400°C, and 500°C. The dimensionless figure of merit (ZT) was calculated using the following equation (2). ZT=S 2 σT / κ (2) where T = absolute temperature (K), κ = thermal conductivity (W / (m×K)).

[0057] [Table 1]

[0058] Compared to Comparative Example 1 in which no boride was added, Inventive Examples 1-5 in which boride was added have a high power factor PF at various temperatures and are confirmed to have excellent thermoelectric properties (power generation performance and thermoelectric conversion efficiency).

[0059] Example 2 Oxidation resistance was evaluated in Example 2. Thermoelectric conversion materials having the compositions shown in Table 2 were obtained by the same production method as in Example 1. The thermoelectric conversion material obtained as described above was subjected to an oxidation heat treatment in which the material was heated to 750° C. in a water vapor atmosphere of 200 Pa and then cooled without any holding time. Samples taken from the thermoelectric conversion material before and after the heat treatment were analyzed by energy dispersive X-ray analysis (EDX) to confirm the composition of the surface. The measurement results are shown in Table 2. Figure 5 shows a photograph of the surface after the heat treatment.

[0060] [Table 2]

[0061] In Comparative Examples 11 and 12, where no boride was added, the oxygen (O) content increased and the silicon (Si) content decreased after heat treatment. This is presumably because magnesium oxide was densely formed on the surface, as shown in Figures 5(c) and (d), making it difficult to detect silicon in magnesium silicide. In contrast, in the present invention examples 11 and 12 in which boride was added, the oxygen (O) content increased slightly after heat treatment, but the magnesium (Mg) and silicon (Si) contents did not change significantly. This is presumably because, as shown in Figures 5(a) and (b), the generation of magnesium oxide was suppressed and sufficient silicon in magnesium silicide was detected.

[0062] The white parts in Figures 5(a) and (b) are magnesium oxides, and the EDX values ​​in Table 2 are the results of measurements taken on areas other than the spherical white parts (ground areas). On the other hand, the entire surface of the sample in the comparative examples (c) and (d) is covered with magnesium oxide, so the analysis was performed on top of this magnesium oxide. The following reaction is thought to be one of the mechanisms by which oxidation of magnesium silicide with added boride is suppressed. First, a part of the boride in contact with magnesium silicide reacts with the magnesium silicide and decomposes into titanium, zirconium, hafnium, or boron, and these elements diffuse into the magnesium silicide particles to form compounds of magnesium and these elements. It is thought that these compounds suppress the diffusion of magnesium to the surface of the thermoelectric conversion material, thereby preventing the oxidation of magnesium silicide. Alternatively, it is thought that these compounds suppress the diffusion of oxygen into the inside of the thermoelectric conversion material, thereby suppressing the oxidation of magnesium silicide.

[0063] Example 3 Strength was evaluated in Example 3. Thermoelectric conversion materials having the compositions shown in Table 3 were obtained by the same manufacturing method as in Example 1. A three-point bending test was carried out on the thermoelectric conversion materials obtained as described above at temperatures in the range of room temperature (25°C) to 550°C shown in Table 3, and the bending strength was measured. In addition, the ratio of the bending strength at 500°C to the bending strength at room temperature (25°C) was calculated. The measurement results are shown in Table 3.

[0064] The three-point bending tester used was a Shimadzu Autograph (AG-25TD). The test fixture was a SiC three-point bending fixture with a support distance of 12 mm. The test atmosphere was air at room temperature and Ar at 300℃ to 550℃. The crosshead displacement rate was 0.5mm / min, the temperature rise rate was 20℃ / min, and the test temperature was held for 15 minutes before the three-point bending test. The bending strength (MPa) was calculated from the maximum load at break using the following formula. Flexural strength (MPa) = 3 / 2 x F max ×L / (t 2 ×W) F max :Maximum load (N), L: Distance between fulcrums (mm) t: test piece thickness (mm), W: test piece width (mm)

[0065] [Table 3]

[0066] In Examples 21-26 of the present invention in which boride was added, the increase in bending strength at high temperature (500°C) relative to bending strength at room temperature (25°C) (bending strength at 500°C / bending strength at 25°C) was sufficiently higher than that in Comparative Example 21. In addition, the bending strength at high temperature (500°C) was also higher than that in Comparative Example 21. The reason for this is believed to be as follows. Generally, the bending strength of borides is 400 MPa at room temperature in Ar, and the strength remains almost constant up to 1400°C when heated. In the sample in this study, the borides aggregated at the grain boundaries to form thin layers that were then sintered. On the other hand, the strength of the bulk body is thought to depend on the strength of the particles and grain boundaries that make up the bulk body. In this study, the three-point bending strength was almost the same at room temperature regardless of whether or not borides were added, so it is thought that the strength is mainly determined by the particle strength of the magnesium silicide.

[0067] When bending tests were performed at a temperature of 500°C, the strength increased from room temperature, but the increase was small when no additive was added, and the strength peaked at an additive amount of approximately 3 mass% to 4 mass%, more than double the strength. This indicates that the strength of the bulk body increased more than the strength of magnesium silicide. The reason for this is thought to be the improved bonding strength between boride particles and magnesium silicide particles that are in contact at the grain boundaries, which led to an increase in bending strength at high temperatures.

[0068] The reason for the peak around 3 mass% to 4 mass% is considered to be as follows. Sintering of borides involves adding sintering aids and going through several processes (including pressure processes such as hot pressing), and finally sintering at a high temperature of around 2000°C. In this study, if the amount of addition is increased to around 10 mass%, the thickness of the grain boundaries formed by the borides will increase, and it is thought that the number of cases where the borides come into contact with each other will increase. However, since the maximum temperature for sintering magnesium silicide is 1020°C and no sintering aids are added, it is thought that the strength of the borides formed at the grain boundaries is smaller than the true strength of the borides. Therefore, if the amount of boride added is too much, the strength will be lower than 4 mass%. Also, if the amount of boride added is less than 3 mass%, the magnesium silicide particles are not sufficiently covered with boride, and the strength is lower than 3 mass%. From another perspective, it is thought that the maximum strength was obtained around 3 mass% to 4 mass%, where magnesium silicide is covered with boride just enough.

[0069] Example 4 Fracture toughness was evaluated in Example 4. Thermoelectric conversion materials having the compositions shown in Table 4 were obtained by the same production method as in Example 1. The fracture toughness Kc of the obtained thermoelectric conversion material was measured by the IF method specified in JIS R 1607. In this example, the measurement was performed by carrying out a micro Vickers test using Shimadzu Corporation's HSV-30 under conditions of room temperature, a test load of 3 kg, and a holding time of 15 seconds. Here, 143 GPa was used as the elastic modulus of the thermoelectric conversion material. (See Japanese Journal of Applied Physics 54, 07JC03 (2015) M. Ishikawa et al.)

[0070] [Table 4]

[0071] In the present invention examples 31 and 32 in which boride was added, the fracture toughness Kc was higher than that of the comparative example 31 in which no boride was added. It was confirmed that the fracture strength was improved by adding boride. It was also confirmed that the fracture toughness Kc increased as the amount of boride added increased.

[0072] Example 5 In this Example 5, the thermoelectric properties of a thermoelectric conversion material in which Al was added to magnesium silicide (Mg2Si) were evaluated. Thermoelectric conversion materials having the compositions shown in Table 5 were obtained by the same manufacturing method as in Example 1. Aluminum powder with a purity of 99.99 mass% (particle size 45 μm: manufactured by Kojundo Chemical Laboratory Co., Ltd.) was used as the raw material. The thermoelectric conversion materials obtained as described above were evaluated for resistivity R, Seebeck coefficient S, and power factor PF at various temperatures in the same manner as in Example 1. The evaluation results are shown in Table 5.

[0073] [Table 5]

[0074] In Examples 41 to 45 of the present invention in which Al was added together with the boride, it was confirmed that the power factor PF was high at various temperatures and the thermoelectric properties (power generation performance) were excellent.

[0075] Example 6 In this Example 6, the oxidation resistance of a thermoelectric conversion material in which Al was added to magnesium silicide (Mg2Si) was evaluated. By the same production method as in Example 5, a thermoelectric conversion material having the composition shown in Table 6 was obtained. The thermoelectric conversion material obtained as described above was subjected to heat treatment in a water vapor atmosphere in the same manner as in Example 2, and samples taken from the thermoelectric conversion material before and after the heat treatment were analyzed by energy dispersive X-ray analysis (EDX) to confirm the composition on the surface. The measurement results are shown in Table 6.

[0076] [Table 6]

[0077] In the present invention examples 51-54, in which boride and Al were added, the oxygen (O) content was slightly increased after heat treatment, but the magnesium (Mg) and silicon (Si) contents did not change significantly. In other words, it was confirmed that the generation of magnesium oxide was suppressed in the present invention examples 51-54 as well.

[0078] Example 7 In this Example 7, Mg2Si X Sn 1-X The thermoelectric properties of a thermoelectric conversion material whose main component is x (where 0.3≦x≦1) were evaluated. Thermoelectric conversion materials having the compositions shown in Tables 7-9 were obtained by the same manufacturing method as in Example 1. Note that tin powder with a purity of 99.99 mass% (particle size 150 μm: manufactured by Kojundo Chemical Laboratory Co., Ltd.) and aluminum powder with a purity of 99.99 mass% (particle size 45 μm: manufactured by Kojundo Chemical Laboratory Co., Ltd.) were used as raw materials. The thermoelectric conversion materials obtained as described above were evaluated for resistivity R, Seebeck coefficient S, and power factor PF at various temperatures in the same manner as in Example 1. The evaluation results are shown in Tables 7-9.

[0079] [Table 7]

[0080] [Table 8]

[0081] [Table 9]

[0082] Mg2Si X Sn 1-X In the thermoelectric conversion material mainly composed of (X=0.4), it is confirmed that in Examples 61 and 62 of the present invention in which boride was added, the power factor PF was high at various temperatures and the thermoelectric properties (power generation performance) were excellent, compared to Comparative Example 61 in which no boride was added. Mg2Si X Sn 1-X In the thermoelectric conversion material mainly composed of (X=0.5), it is confirmed that in Examples 71-74 of the present invention in which boride was added, the power factor PF was high at various temperatures and the thermoelectric properties (power generation performance) were excellent, compared to Comparative Examples 71 and 72 in which no boride was added. Mg2Si X Sn 1-X In the thermoelectric conversion material mainly composed of (X=0.35), it is confirmed that in Examples 81 to 84 of the present invention in which boride was added, the power factor PF was high at various temperatures and the thermoelectric properties (power generation performance) were excellent, compared to Comparative Example 81 in which no boride was added.

[0083] Example 8 In this Example 8, Mg2Si X Sn 1-X(where 0.3≦X≦1) as the main component, the hardness, toughness, and strength of the thermoelectric conversion material were evaluated. A thermoelectric conversion material having the composition shown in Table 10 was obtained by the same manufacturing method as in Example 1. Note that tin powder with a purity of 99.99 mass% (particle size 150 μm: manufactured by Kojundo Chemical Laboratory Co., Ltd.) and aluminum powder with a purity of 99.99 mass% (particle size 45 μm: manufactured by Kojundo Chemical Laboratory Co., Ltd.) were used as raw materials. The thermoelectric conversion materials obtained as described above were evaluated for Vickers hardness, the length of the crack formed at the edge of the indentation during the Vickers hardness test, and the bending strength during three-point bending in the same manner as in Examples 3 and 4. The evaluation results are shown in Table 10.

[0084] [Table 10]

[0085] Mg2Si X Sn 1-X In the thermoelectric conversion material mainly composed of (X=0.4), it is confirmed that the Vickers hardness and bending strength are higher in the invention examples 91 and 92 to which boride is added than in the comparative example 91 to which no boride is added. It is also confirmed that the crack length is short and the fracture toughness is excellent. Mg2Si X Sn 1-X In the thermoelectric conversion material mainly composed of (X=0.5), it is confirmed that the Vickers hardness and bending strength are higher in the invention examples 93 and 94 to which boride is added than in the comparative example 93 to which no boride is added. It is also confirmed that the crack length is short and the fracture toughness is excellent. Mg2Si X Sn 1-X In the thermoelectric conversion material mainly composed of (X=0.35), it is confirmed that the Vickers hardness and bending strength are higher in Example 95 of the present invention to which boride is added than in Comparative Example 95 to which no boride is added. It is also confirmed that the crack length is short and the fracture toughness is excellent.

[0086] From the above, it was confirmed that the present invention can provide a thermoelectric conversion material having excellent thermoelectric properties, oxidation resistance, and strength. [Explanation of symbols]

[0087] 1 Thermoelectric conversion module 10 Thermoelectric conversion element 11 Thermoelectric materials 18a,18b electrode 19a, 19b terminals

Claims

1. Mg 2 S X Sn 1-X (wherein 0.35≦X≦1) and a boride containing one or more metals selected from titanium, zirconium, and hafnium; A thermoelectric conversion material, characterized in that a total content of the borides in the thermoelectric conversion material is within a range of 3.0 mass% or more and 9.8 mass% or less.

2. The Mg 2 S X Sn 1-X 2. The thermoelectric conversion material according to claim 1, characterized in that x is magnesium silicide with x=1.

3. The boride is TiB 2 , ZrB 2 , HfB 2 3. The thermoelectric conversion material according to claim 1, wherein the thermoelectric conversion material is one or more selected from the following:

4. The thermoelectric conversion material according to any one of claims 1 to 3, further comprising aluminum, the content of the aluminum being within a range of 0.05 mass% or more and 1 mass% or less relative to the thermoelectric conversion material.

5. A thermoelectric conversion element comprising a thermoelectric conversion material described in any one of claims 1 to 4 and electrodes joined to one side and the other opposing side of the thermoelectric conversion material.

6. A thermoelectric conversion module comprising the thermoelectric conversion element described in claim 5 and terminals respectively joined to the electrodes of the thermoelectric conversion element.

Citation Information

Patent Citations

  • Dispersively reinforcing material

    JP1991166335A

  • N-type thermoelectric conversion material and manufacturing method thereof

    JP2001274464A

  • Mg2Si1-xSnx-BASED POLYCRYSTALLINE MATERIAL AND PRODUCING METHOD THEREOF

    JP2013008747A

  • Thermoelectric conversion material, production method therefor and thermoelectric conversion element

    JP2013179322A

  • Composite body and thermoelectric transducer including same

    JP2016164960A